1995
DOI: 10.1080/02681219580000781
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis in a renal transplant recipient

Abstract: Paracoccidioidomycosis is a fungal infection rarely described in immunodeficient patients. We report a severe case of pulmonary paracoccidioidomycosis in a renal transplant recipient and demonstrate deficiencies of in vitro lymphocytic transformation assays, skin hypersensitivity tests, as well as low levels of antibodies to Paracoccidioides brasiliensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 6 publications
0
23
0
4
Order By: Relevance
“…Only three cases of paracoccidioidomycosis in SOT recipients have been reported, and all occurred in renal transplant patients (339,353,417). In all cases, infection developed more than 5 years after transplantation, and clinical presentations were similar to those of other cases of this mycosis in nonimmunosuppressed patients.…”
Section: Other Regional Fungal Infectionsmentioning
confidence: 93%
“…Only three cases of paracoccidioidomycosis in SOT recipients have been reported, and all occurred in renal transplant patients (339,353,417). In all cases, infection developed more than 5 years after transplantation, and clinical presentations were similar to those of other cases of this mycosis in nonimmunosuppressed patients.…”
Section: Other Regional Fungal Infectionsmentioning
confidence: 93%
“…PCM in solid organ transplant patients was firstly reported in 1984 7 . Since then, just another case was reported 6 . The present case is the third one reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of the first case was similar to other cases of the mycosis in non-immunosuppressed patients 7 . SHIKANAI-YASUDA et al 6 reported a case with severe pulmonary infection. In our report, clinical manifestations of the disease were similar to nonimmunosuppressed patients infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pmycosis has been described in immunosuppressed patients on cancer treatment and after renal transplantation (Sugar et al, 1984;Shikanai-Yasuda et al, 1995). There are reports of Pmycosis in patients using corticosteroids, azathioprine, and antineoplastic drugs (Londero et al, 1987).…”
Section: Paracoccidioidomycosis In the Immunocompromised Personmentioning
confidence: 99%